2016
DOI: 10.5014/ajot.2016.021535
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Patterns, Obesity, and Physical Activity Participation of Children With Autism Spectrum Disorder

Abstract: Obesity is a public health concern for the population in general and for children with autism spectrum disorder (ASD) specifically. The purpose of this study was to understand relationships between sensory patterns, obesity, and physical activity engagement of children with ASD (N = 77) sampled from a specialized community-based swimming program. This retrospective correlational study analyzed program data. Results show that almost half (42.2%) of the children were overweight or obese, and sensory avoiding beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
9
1
3
Order By: Relevance
“…Our findings showed a significant negative relationship between sensory sensitivity and BMI, indicating children with lower thresholds for sensory stimuli had lower BMI. This finding is inconsistent with research reporting that children with avoiding preferences have a higher BMI (Lawson & Foster, 2016) and that there is a weak correlation between adults with sensory-seeking preferences and lower BMI (Kimball, Birstler, Bosse, Nelson, & Woods, 2012). Previous research suggested the relationships between sensory preferences and BMI might be explained by the level of engagement with physical activity.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Our findings showed a significant negative relationship between sensory sensitivity and BMI, indicating children with lower thresholds for sensory stimuli had lower BMI. This finding is inconsistent with research reporting that children with avoiding preferences have a higher BMI (Lawson & Foster, 2016) and that there is a weak correlation between adults with sensory-seeking preferences and lower BMI (Kimball, Birstler, Bosse, Nelson, & Woods, 2012). Previous research suggested the relationships between sensory preferences and BMI might be explained by the level of engagement with physical activity.…”
Section: Discussioncontrasting
confidence: 79%
“…Our study's findings were in complete contrast to previous research (Bickham et al, 2013; Ferrar, Chang, Ming, & Olds, 2013), as study participants reported engaging in similar levels of physical activity despite BMI and sensory patterns. Differences may be explained by the study samples, as Lawson and Foster (2016) studied children with autism spectrum disorders, Kimball et al (2012) studied typically developing adolescent and adult women, and our sample comprised healthy, typically developing adolescents. It is also possible the relationship between BMI and sensory patterns is influenced by mediating factors, such as diet (Bohnert et al, 2013;Ferrar, Olds, Maher, & Maddison, 2013;Periwal & Chow, 2006) and sleep patterns (Golley, Maher, Matricciani, & Olds, 2013;Kjeldsen et al, 2013;Miller, Lumeng, & LeBourgeois, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to possible deficits in proprioception, people with ASD demonstrate more variable patterns of functional difficulties and responsiveness to sensory events [Kientz & Dunn, 1997]. This altered sensory processing (auditory, visual, tactile, and movement) is suggested to affect participation in everyday activities including physical activity [Lawson & Foster, 2016;Little, Dean, Tomchek, & Dunn, 2018] and the learning of new concepts [Brown & Dunn, 2010]. Moreover, sensory processing patterns may be associated with preferences for different activities [Ismael, Lawson, & Cox, 2015] and the level of difficulty (considering individual experiences).…”
Section: Discussionmentioning
confidence: 99%
“…For example, autistic adults in our sample had significantly greater odds of metabolic disorders. Evidence from younger autistic populations suggests that multiple factors increase risk for metabolic disorders including prescription psychotropic drugs (Shedlock et al, 2016), sensory motor challenges that can reduce physical activity (Lawson & Foster, 2016), sensory preferences that can limit food choices (Polfuss et al, 2016), and sleep disturbances (Zuckerman et al, 2014). However, healthcare providers who treat older autistic adults may not be aware of the various factors contributing to obesity in this population, which likely necessitate a specialized approach to weight management.…”
Section: Implications For Healthcare Deliverymentioning
confidence: 99%